Research proposal on English Reading Comprehension Text Level Difficulties among Saudi Science students - Sajid, Muhammad Khalid Mehmood; Hafizoah, Kassim; Al Fraidan, Abdullah; Hasan, Ghassan Adnan; Iqbal, Zafar; Aljarrah, Khaled; Al Anazi, Nawaf (PalArch Foundation, 2020)
The overall objective of the project was to evaluate the issues of the English reading comprehension text level among Saudi Science students at the King Faisal University English Language Centre to improve the reading comprehension of science students with reading text problems. In relation to the multiple text level problems students have in reading comprehension, the literature of the prescribed material was chosen for text levels. The research explored the unique problems in the text of the learning material affecting these students. The participants were 120 Saudi science students at ELC with reading problems who had to participate in this study. In the proposal for convenience sampling, a mixed approach was proposed. SPSS program was also suggested by the researcher to evaluate the quantitative date that included questionnaire and an experimental study.However, Atlas ti 7 was recommended to analyze qualitative themes of the interview. Within three years, the planned PhD research had to be carried out. The main objective of the study was to evaluate the difference between difficulties in reading text level and strategies used to resolve the King Faisal University ELC among Saudi students.